The Role Of Information Technology And Work Environment In Improving Teacher Performance - Wahna Widhianingrum; Ranti Kurniasih; Riawan Riawan (Universitas Lambung Mangkurat, 2024)
This research was carried out to determine the influence of the work environment and the use of information technology on teachers' performance as educators in this era of digitalization, where effectiveness in the use of information technology and support in the form of an adequate work environment. This research uses a type of quantitative descriptive research using a research instrument in the form of a questionnaire. The respondents of this research were 45 teachers at SMA Muhammadiyah 1 Ponorogo. Based on age, the majority of the productive period is 37.8%, the remainder are seniors, and most teaching staff at the school are female. The length of work of respondents in this study is 0-10 years, which is more dominant. The level of teacher education is good, and the bachelor's and master's levels of education can support teacher performance. The ability to use information technology and the physical work environment truly reflects the situation and conditions that exist in the school and plays an active role in assisting the learning process and helping improve teacher performance when carrying out their duties.